Determinan Kepuasan Pengguna Software Akuntansi - Agustini, Luh De Leony; Juliarsa, Gede (E-Jurnal Akuntansi; Vol 34 No 2 (2024)DO - 10.24843/EJA.2024.v34.i02.p05, 2024)
This study examines the influence of the Quality of Accounting Information Systems, Perceived Usefulness, Perceived Ease of Use on Accounting Software User Satisfaction at PT. Sejahtera Indo Bali, with a sample of 42 people. By using multiple linear regression analysis, the findings prove that the quality of accounting information systems and perceived ease of use have a positive effect on user satisfaction of accounting software, while perceived usefulness does not have a positive effect on user satisfaction of accounting software. In addition, the Technology Acceptance Model (TAM) model is able to explain the factors that influence user satisfaction with accounting software. Keywords: Accounting Information System Quality; Perceived Usefulness; Perceived Ease Of Use